Cell-Free Spent Media Obtained from Bifidobacterium bifidum and Bifidobacterium crudilactis Grown in Media Supplemented with 3′-Sialyllactose Modulate Virulence Gene Expression in Escherichia coli O157:H7 and Salmonella Typhimurium - Bondue, Pauline; Crèvecoeur, Sébastien; Brose, François; Daube, Georges; Seghaye, Marie-Christine; Griffiths, Mansel W.; LaPointe, Gisèle; Delcenserie, Véronique (Frontiers in Microbiology, 2016)
Complex oligosaccharides from human milk (HMO) possess an antimicrobial activity and can promote the growth of bifidobacteria such as Bifidobacterium bifidum and Bifidobacterium longum subsp. infantis. In addition, fermentation of carbohydrates by bifidobacteria can result in the production of metabolites presenting an antivirulence effect on several pathogenic bacteria. Whey is rich in complex bovine milk oligosaccharides (BMO) structurally similar to HMO and B. crudilactis, a species of bovine origin, is able to metabolize some of those complex carbohydrates. This study focused on the ability of B. bifidum and B. crudilactis to grow in a culture medium supplemented in 3’-sialyllactose (3’SL) as sole source of carbon, a main BMO encountered in cow milk. Next, the effects of cell-free spent media (CFSM) were tested against virulence expression of Escherichia coli O157:H7 and Salmonella enterica serovar Typhimurium. Both strains were able to grow in presence of 3’SL, but B. crudilactis showed the best growth (7.92 ± 0.3 log cfu/ml) compared to B. bifidum (6.84 ± 0.9 log cfu/ml). Then, CFSM were tested for their effects on virulence gene expression by ler and hilA promoter activity of luminescent mutants of E. coli and S. Typhimurium, respectively, and on wild type strains of E. coli O157:H7 and S. Typhimurium using RT-qPCR. All CFSM resulted in significant under expression of the ler and hilA genes for the luminescent mutants and ler (ratios of -15.4 and -8.1 respectively) and qseA (ratios of -2.1 and -3.1) for the wild type strain of E. coli O157:H7. The 3’SL, a major BMO, combined with some bifidobacteria strains of bovine or human origin could therefore be an interesting synbiotic to maintain or restore the intestinal health of young children. These effects observed in vitro will be further investigated regarding the exact nature of the active molecules.